2020
DOI: 10.1002/anie.202004769
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of (−)‐Minovincine and (−)‐Aspidofractinine through a Sequence of Cascade Reactions

Abstract: We report 8‐step syntheses of (−)‐minovincine and (−)‐aspidofractinine using easily available and inexpensive reagents and catalyst. A key element of the strategy was the utilization of a sequence of cascade reactions to rapidly construct the penta‐ and hexacyclic frameworks. These cascade transformations included organocatalytic Michael‐aldol condensation, a multistep anionic Michael‐S N 2 cascade reaction, and Mannich reaction interrupted Fischer indolization. To streamline the synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 70 publications
(2 reference statements)
0
24
0
Order By: Relevance
“…25,26 However, there are few examples in the literature for the enantioselective total synthesis of (−)-minovincine. 27–29 Based on our present approach and interest in synthesis of natural alkaloids, 30 the cis -hydroindole scaffold present in minovincine inspired us to develop a concise synthetic route for the enantioselective formal total synthesis of the naturally occurring enantiomer (+)-minovincine. As shown in Scheme 3, the enantiomerically pure product 3a was readily reduced to 4 in 92% yield with 97% ee by treatment with 5 mol% Crabtree's catalyst under a hydrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 However, there are few examples in the literature for the enantioselective total synthesis of (−)-minovincine. 27–29 Based on our present approach and interest in synthesis of natural alkaloids, 30 the cis -hydroindole scaffold present in minovincine inspired us to develop a concise synthetic route for the enantioselective formal total synthesis of the naturally occurring enantiomer (+)-minovincine. As shown in Scheme 3, the enantiomerically pure product 3a was readily reduced to 4 in 92% yield with 97% ee by treatment with 5 mol% Crabtree's catalyst under a hydrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of 10 was determined to be opposite to that reported by Soós, and then it could be converted into (+)-minovincine in three steps according to a known procedure. 29…”
Section: Resultsmentioning
confidence: 99%
“…Stepwise addition–cyclization methods, including isolation of the aziridine-opened intermediates, have been reported by using the NH-free aziridine and α,β-unsaturated ketones . Recently, a cascade reaction including the S N 2 reaction of NH-free aziridine to an alkyl halide, aziridine-opening chlorination, and intramolecular conjugate addition of the resulting NH group was achieved in the total synthesis of (−)-minovincine and (−)-aspidofractinine . In our course of synthetic studies on alkaloids, we found that lithium iodide mediated the [3 + 2] addition reaction of nonsubstituted N -tosylaziridine with an α,β-unsaturated ketone to achieve the direct construction of N -tosylpyrrolidine.…”
mentioning
confidence: 99%
“…Recently, our laboratory developed a short and scalable (60g) synthetic route for the stereoselective synthesis of Aspidosperma tricyclic ketone core 7 with C-5 methoxycarbonyl group and employed this advanced intermediate for the concise syntheses of (−)-minovincine ( 2 ) and (−)-aspidofractinine ( 3 ) ( Scheme 1 ). 7 A key element of these syntheses was the rapid buildup of much of the complexities of the targets through the sequence of organocascade and anionic cascade reactions. These routes are strategically aligned with the Stork–Dolfini synthesis 3a of aspidospermidine but delivering C-20 oxidized intermediates and natural products.…”
mentioning
confidence: 99%